PENANGANAN PENGADUAN MASYARAKAT SEBAGAI PENDUKUNG IKLIM ORGANISASI (Studi Deskriptif Kualitatif Penanganan Pengaduan Masyarakat di Seksi Informasi dan Sarana Komunikasi Kantor Imigrasi Kelas I Y ogyakarta) - Widya Larasati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Complaint handling becomes an important thing that can be a medium to improve the quality of work or services in an organization. This research describes about complaint handling in Information and Communication section as the division that handles the complaint received by Imigrasi Kelas I Yogyakarta office. Complaints that received by organization can affect the employees’ work. This research illustrates how public complaint handling supports the organizational climate in this section (Information and Communication section). The positive organizational climate can affect the quality of employees performance, so that the better service will be provided by organizationThis research uses qualitative descriptive method. The data wascollected using observation, in-depth interview and documentation. To check the validity of the data, the author uses a triangualtion of sources.The result of this research shows that public complaint handling supports the organizational climate in this section in accordance with the dimension of organizational climate of Stringer which include structure, standards, responsibility, recognition, support and commitment. Organizational climate in this section becomes pleasant because the employees feel that they have high responsibility to face and finish the complaints, support each others and look for a solution together. Moreover, the proudness of their work, motivation to do the better work and loyality toward organization increase because of those public complaint handling.